Overcoming Product Catalog Challenges in Telecom : A Technical Perspective - Anirudha Shekhar Karandikar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article explores the intricate challenges telecom providers face in managing complex product catalogs across multiple customer touchpoints. With the global telecom market projected to reach $2.47 trillion by 2028, efficient catalog management is crucial for maintaining competitiveness and customer satisfaction. The article delves into the multifaceted complexities of telecom product catalogs, including regional pricing variations, dynamic promotional offers, and the need for real-time synchronization across platforms. It outlines key challenges such as catalog complexity, slow data retrieval, frequent updates, third-party integration latencies, high traffic spikes, and campaign management inconsistencies. The article then presents innovative technical solutions and best practices, including the adoption of industry-leading catalog solutions, leveraging ElasticSearch for faster data retrieval, implementing differential processing for updates, preprocessing third-party integrations, utilizing dynamic UI templates, employing advanced campaign management tools, and implementing inventory prefetching. These solutions aim to enhance operational efficiency, improve customer experiences, and accelerate time-to-market in the rapidly evolving telecom industry.
Keywords: Catalog Management Challenges; Real-time Synchronization; Telecom Product Catalogs; Technical Solutions; Customer Experience Optimization